Multifamily Renting System - M. Divyapushpalakshmi; S. Lavanya; M.Moneshkumar; N. Darshan (International Journal of Psychosocial Rehabilitation, 2020)
The housing domain is careful in facing the challenges by introducing a new strategy that facilitates the comfortable administration of rental flats. A rental management system is required to make the work simple for property managers. So that we decided to develop a system that enables the managers to do their work in an efficient manner. The system facilitates separate login for the property managers and the renters. The managers can add the details about the available flats along with the following details: number of rooms, floors, and rents for the flat, and he also mentions the availability of him so that the users can go to visit the flats accordingly. Users can register with the website by providing the basic details and they can login to view the flat details that were added by the manager. If the user is interested in the flat, then he/she can go directly to view the flats by knowing the manager’s availability. Once they reach the place, to get the flat key, the user needs to enter the OTP that is sent to the registered mobile number. Along with the OTP, the user needs to enter their credit card number to debit the amount from the user account if they caused any damage in the flat. After the visit, the user can post their reviews on the website which the manager can view and make any further advancement. With this system, the user can get multiple choices for renting and the manager can increase their customer